2012
DOI: 10.1152/ajpcell.00368.2011
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial functional specialization in glycolytic and oxidative muscle fibers: tailoring the organelle for optimal function

Abstract: Picard M, Hepple RT, Burelle Y. Mitochondrial functional specialization in glycolytic and oxidative muscle fibers: tailoring the organelle for optimal function. Am J Physiol Cell Physiol 302: C629 -C641, 2012. First published October 26, 2011; doi:10.1152/ajpcell.00368.2011In skeletal muscle, two major types of muscle fibers exist: slow-twitch oxidative (type I) fibers designed for low-intensity long-lasting contractions, and fast-twitch glycolytic (type II) fibers designed for high-intensity short-duration c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
128
3
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 172 publications
(149 citation statements)
references
References 129 publications
7
128
3
1
Order By: Relevance
“…Previous studies demonstrated that the localization of nuclei is crucial for proper muscle performance (Metzger et al, 2012) and that mitochondria are highly organized in muscles (Picard et al, 2012). The accumulation of CryAB around the nuclei (Fig.…”
Section: Cryab Is Required For Z-band Patterning and Muscle Integritymentioning
confidence: 83%
“…Previous studies demonstrated that the localization of nuclei is crucial for proper muscle performance (Metzger et al, 2012) and that mitochondria are highly organized in muscles (Picard et al, 2012). The accumulation of CryAB around the nuclei (Fig.…”
Section: Cryab Is Required For Z-band Patterning and Muscle Integritymentioning
confidence: 83%
“…Type I, type IIa, and type IIx predominantly use oxidative respiration for energy production, while type IIb mainly uses glycolysis (43,44). Overexpression of AKT1 in skeletal muscle causes muscle hypertrophy and increased type IIb muscle (glycolytic) fibers (15).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to its role in apoptosis, transient opening of the mPTP in a low-conductance mode that allows diffusion of ions but not higher molecular weight solutes serves a physiological function (113). Indeed, such mPTP flickering is suggested to 1) serve as a Ca 2ϩ release valve to regulate mitochondrial Ca 2ϩ levels and likely cellular Ca 2ϩ transients (45); 2) provide a means to rapidly and reversibly depolarize mitochondria, possibly controlling their autophagic removal (44); 3) modulate superoxide production since transient mPTP opening yields superoxide flashes in myocytes (156); and 4) allow the release from the mitochondrial matrix into the cytoplasm of other molecules including the nicotinamide adenine nucleotides (NAD ϩ and NADH) (42) and possibly metabolic intermediates (see first 5 headings under Mitochondrial Retrograde Signaling).…”
Section: Mitochondrial Structure-function Relationshipmentioning
confidence: 99%